Synthesis of graphene by pullulan-assisted exfoliation of graphite using ultrasonic bath - Nurul Farhana, Abu Kasim (2021)
Graphene is the carbon basis for all graphitic dimensionalities like graphite, carbon nanotube (CNT), fullerene, and others. Interestingly, graphene can be exfoliated from graphite using a suitable solvent that acts as an exfoliating medium. Since most of the organic solvents used in the graphene synthesis like N-methyl-2-pyrrolidone (NMP) and Dimethylformamide are toxic and carcinogenic, an environment-friendly solvent was used to counter the problem. Previously, polysaccharides such as Arabic gum, chitosan, and sodium alginate were employed as solvents to produce graphene. However, the majority of these polysaccharides have high viscosity, which makes graphite exfoliation and washing process difficult. Therefore in this thesis, a lower viscosity polysaccharide which is pullulan was selected as a green dispersant in assisting the exfoliation of graphite in order to produce graphene under ultrasonic bath conditions. The chemical properties of pullulan-based graphene (graphene) was confirmed by utilizing Ultraviolet-Visible Spectroscopy (UV-vis), X-Ray Photon Spectroscopy (XPS), and Fourier Transformation Infrared Spectroscopy (FTIR). Meanwhile, Raman Spectroscopy, Transmission Electron Microscopy (TEM), and Atomic Force Microscopy (AFM) were used to study the structural analysis of graphene. From the UV-vis tested, the result proved the presence of graphene at a wavelength of 269nm. The XPS also reveals high carbon content with a value of 4.7 carbon to oxygen ratio (C:O). As expected, from the FTIR analysis, the existence of C=C and –OH peaks in the graphene was observed after the exfoliating process. Notably, a small defect intensity (ID/IG) of graphene was obtained from Raman Spectroscopy. The lateral size and thickness of the exfoliated graphene were measured by TEM and AFM at the range of 201 - 300 nm and ~2 nm (5 layers) respectively. To study the optimum condition to produce a high yield of graphene, the effect of processing parameters such as duration of sonication, pullulan, and initial mass of graphite were taken into account. The graphene was then enforced as a sensing element for graphene photo paper to demonstrate the use of graphene. Scanning Electron Microscopy (SEM) was used to investigate the morphology of the graphene photo paper. In order to get the mechanical and electrical properties of the graphene photo paper, tensile tests and multimeter have been utilized accordingly. The reinforcement of graphene in photo paper enhanced the tensile strength up to 21%. Impressively, the electrical performance of the graphene photo paper with 140gauge factor (GF) implies that the pullulan-based graphene could be applied as an electrically conductive ink. Overall, this work would represent the simplest, most environmentally friendly and most efficient strategy for the toxic-free graphene preparation and the development of photo paper for graphene-based strain sensor.